Konsep Pendidikan Inklusif dalam Perspektif Islam - Munawir; Hilda Khilmatul Maulidiyah; Saila Arrochmah (Jurnal Pendidikan Islam, 2024)
The concept of inclusive education is an educational concept that represents all aspects related to openness in accepting children with special needs in order to achieve their basic rights as citizens. Inclusive education is presented to support the education of children who need special assistance in obtaining education. The purpose of this research is to find out about the Islamic perspective on inclusive education. The method used in this research is to use qualitative methods because the data produced is in the form of words or descriptions. The type of research used in this research is using literature studies. The results of this study indicate that inclusive education programs in schools bring together students in classes in the same educational environment and with the same services. In the Qur'an there are verses that refer to the development of an inclusive education system in the context of Islamic education. Inclusive education provides lessons on the value of humanity, the value of diversity, social justice, tolerance and care. The concept of inclusive education in an Islamic perspective can also be expressed as a form of effort to improve and replace bad character with good character in one's perspective towards children with special needs.